Adult murine cardiomyocytes exhibit regenerative activity with cell cycle reentry through STAT3 in the healing process of myocarditis - Akimitsu Miyawaki (Nature Portfolio, 2017)
Abstract Mammalian cardiomyocytes substantially lose proliferative capacity immediately after birth, limiting adult heart regeneration after injury. However, clinical myocarditis appears to be self-limiting with tissue-reparative properties. Here, we investigated the molecular mechanisms underlying the recovery from myocarditis with regard to cardiomyocyte proliferation using an experimental autoimmune myocarditis (EAM) model. Three weeks after EAM induction (EAM3w), cardiac tissue displayed infiltration of inflammatory cells with cardiomyocyte apoptosis. However, by EAM5w, the myocardial damage was remarkably attenuated, associated with an increase in cardiomyocytes that were positively stained with cell cycle markers at EAM3w. Cardiomyocyte fate mapping study revealed that the proliferating cardiomyocytes primarily derived from pre-existing cardiomyocytes. Signal transducer and activator of transcription 3 (STAT3) was robustly activated in cardiomyocytes during inflammation, accompanied by induction of interleukin-6 family cytokines. Cardiomyocyte-specific ablation of STAT3 gene suppressed the frequency of cycling cardiomyocytes in the recovery period without influencing inflammatory status, resulting in impaired tissue repair and cardiac dysfunction. Finally, microarray analysis revealed that the expression of regeneration-related genes, metallothioneins and clusterin, in cardiomyocytes was decreased by STAT3 gene deletion. These data show that adult mammalian cardiomyocytes restore regenerative capacity with cell cycle reentry through STAT3 as the heart recovers from myocarditis-induced cardiac damage.